Epistemology of Islamic Education: Criticism and Alternative Solutions - Hellen Tiara; Danu (HEUTAGOGIA: Journal of Islamic Education, 2023)
The purpose of this study is to critique the epistemology of Islamic education in the 21st century, analyze existing problems, and propose alternative solutions. This research employs a qualitative approach, using descriptive analysis methods and a literature review to explore various discussions on the epistemology of Islamic education. Data is validated through source triangulation and then analyzed through collection, presentation, and conclusion drawing. The findings indicate that, despite rapid advancements in education due to technology and globalization, there remain unresolved issues. Critiques of Islamic education epistemology still focus on the dominance of source and tool aspects in studying Islamic epistemology, which tends to be static and non-exploratory. Proposed solutions include an emphasis on empirically-based epistemology, theoretical intellectual knowledge, and a focus on student creativity. Furthermore, in the development of Islamic education curriculum, aspects that are dogmatic and transcendental need to be connected with the empirical world. This research has limitations in terms of scope and depth of analysis, but it has practical implications for the development of more relevant and contextual Islamic education.